After the text
1 online resource.
Keywords: "After the Text honours the work of renowned historian Margaret Mullett, who since the 1970s has transformed the study of Byzantine literature. Her work has been influential in demonstrating the strength and variety of Byzantine texts. Byzantium is renowned for its achievements in architecture and the visual arts. Professor Mullett's perceptive studies, produced over more than 40 years, have shown that the literature of the Byzantine Empire is of equal beauty and interest, ranging, as it does, from high-style poetry and rhetoric in the classical manner through letters to demotic writings such as fables and the lives of saints. The collection of essays in this volume draws further attention to the wealth and diversity of Byzantine texts, by exploring the Greek literature of Late Antiquity and the Middle Ages in all its variety. These studies, by going, like Professor Mullett herself, beyond the texts, illustrate the value of Byzantine literature for interpreting Byzantine history and civilisation in all its richness. This book is crucial reading for scholars and students of the Byzantine world, as well as for those interested in literary studies"--